American General Election 2020: Why Trump Failed and What to Expect From Biden? - Mai, Nguyen Nhu; Van, Chu Thanh (VNU Journal of Foreign Studies, 2021)
The failure in the US election 2020 has ended the former US president Donald Jr. Trump’s efforts in “making America great again”. This article looks at the gains and losses to the USA during his heated time in the office, seeking for the reason for his failure in the general election and forecasting short-term visions of this powerful nation under the newly-elected Joe Biden’s presidency. The results from this discussion paper has shown that the former US president Donald Jr. Trump set off his office term impressively but the final year stopped his progress and even erased most of his efforts with unexpected incidents. The candidate from the Democratic Party, Joe Biden was therefore supported greatly by both the people and the “right time” to get into the White House without much difficulty. However, in regard to the contemporary international and domestic situations, the USA under the newly-elected president Joe Biden’s leadership is expected to confront a considerably hard time in the next four years. As a large-scale economy, the USA’s influences and effects on other countries around the world deserve to be examined more carefully than ever.